State of Formation of Motivation as one of the Structural-functional Components of Speech Development of Primary Schoolchildren with Dysgraphia - Zhuravlova, Larysa; Sheremet, Maria; Dmytriieva, Iryna; Suprun, Daria (International Journal of Psychosocial Rehabilitation, 2020)
The article presents the results of the research of motivation as one of the structural-functional components of speech development of primary schoolchildren with dysgraphia. The role of motivation in the process of human activity and the development of mental functions are emphasized. It is noted that the research of speech activity has to include the study of special features and a motivational aspect of the corresponding activity. The author of the article draws attention to the necessity of the research of this issue especially among primary schoolchildren with dysgraphia. The features of motivation development among primary schoolchildren with dysgraphia are identified. Empirical research, aimed at the examination of the criteria of the motivational component of speech development of such category of primary schoolchildren, has been carried out. It has been experimentally proven that primary schoolchildren with dysgraphia tend to have a decrease of interest and a positive attitude towards learning: there is an increase in the percentage of children who have a neutral attitude towards learning, which leads to a decrease in their level of academic achievements. It has been found out that the indicators of motivational component formation of a majority of 2nd form learners with dysgraphia are lower than medium (59.5%), and the highest number of learners with dysgraphia of the 3rd form have a medium level (62.8%) of motivational component formation. Very few changes have been observed in the increase in the level of motivation among the 3rd form learners.